Temples at the northeast corner of Banganga Tank - Ghosh, Ayan (2023)
Temples at the northeast corner of Banganga Tank; (from left to right) Mahalakshmi Temple (yellow wall), Vyankatesh Balaji Temple (white dome), Jagannnath Mahadeo Temple (white shikara), and Siddheshwar Temple (yellow shikhara). Over time, the addition of new buildings and encroachments have blocked the view of the temples from the ghats.